EDUCATION OF YOUTH IN THE SPIRIT OF HUMANITY - Khikmatov Fakhrullo Fatulloevich (Galaxy International Interdisciplinary Research Journal, 2024)
This article talks about the importance of educating young people in the spirit of humanism, providing them with religious and secular education.